Roxanne Dunbar-Ortiz's Indigenous peoples' history of the United States : a graphic interpretation - Peart-Smith, Paul; Buhle, Paul, 1944-; Davis, Dylan; Dunbar-Ortiz, Roxanne, 1938- (The Revisioning History Series from Beacon Press, 2024)
"In 2014 Roxanne Dunbar-Ortiz's four-hundred-year history brought the brutal legacy of settler colonialism and genocide to the forefront of this nation's collective consciousness. Now her New York Times best-selling book is brought to life in this stunning color graphic adaptation by Paul Peart-Smith"--